Transformation of Zinnia elegans Jacq. as an ornamental potted plant by daminozide application - Nurul Annisa; Aziz Purwantoro; Dyah Weny Respatie (Jurnal Ilmu Pertanian, 2021)
Zinnia elegans Jacq. is one of the ornamental plants potential to be used as a potted ornamental plants. The problem to be resolved is the size of the plant can reach 1 m, so it is necessary to modify the plant height into 20 cm to 25 cm using retardant (plant growth regulator), called daminozide. The purpose of this study was to determine the best concentration and soaking time using daminozide to inhibit the growth of zinnia. The research was conducted at Mangkuyudan 57, Yogyakarta. This research was arranged in a factorial design with 3 blocks as replication. Different concentrations of daminozide were used as first factor with three levels (1 g.L-1, 2 g.L-1, and 3 g.L-1) and soaking times were used as the second factor (12 h, 24 h, and 36 h). The data were analyzed using analysis of variance and continued with HSD-Tukey at the α = 5 %. The results showed that there were an interaction between daminozide concentration and soaking time in the height of Z. elegans. There were also positive correlation between plant height, number of flower, and flowering period. The best combination of daminozide concentration and soaking times were 2 g.L-1 and 12 h. This treatment gave the best height that fit to the criteria of a potted plant which was 20.08 cm. However, it reduced flower’s diameter, number of flowers, and canopy’s size.